Synthesis and characterisation of magnetic-polyethyleneimine-cellulose adsorbent for reactive black 5 dye removal - Nordin, Abu Hassan (2019)
The application of adsorption method for removing dye from textile wastewater has been recognised and adsorption onto conventional activated carbon is known to be the best prospect in eliminating dye that exhibits colour in water. However, activated carbon is costly and inconvenient for regeneration process. Thus, alternative adsorbents have been investigated. It is well-known that the waste materials from agriculture can be obtained and employed as low-cost adsorbents. In this study, cellulose from oil palm empty fruit bunch was modified with polyethyleneimine (PEI) and magnetic nanoparticles via crosslinking method to remove reactive black 5 (RB5) dye. The best conditions to prepare the magnetic-PEI-cellulose adsorbent were investigated and the results obtained for cellulose to PEI ratio is 2:1, impregnation time is 6 hours, crosslinking contact time is 60 mins, volume of glutaraldehyde is 1 ml and cellulose-PEI to magnetic nanoparticles ratio is 2:1:0.25. Then, the synthesised magnetic-PEI-cellulose was characterised using Fourier transform infrared spectroscopy, Brunauer Emmett Teller surface area, vibrating sample magnetometer and point of zero charge. A batch adsorption experiment was conducted and the results obtained were excellent, with almost 100% RB5 removal under the following conditions: 180 min of contact time, 0.1 g of adsorbent, 0.1 g/L of initial RB5 concentration, pH 7 and at 27°C. Kinetics, isotherm and thermodynamics evaluation were also performed for the adsorption data. The adsorption data fitted well to the pseudo second order model with the influence of intraparticle diffusion. For isotherm study, the data best fitted to the Langmuir model (x2 = 3.478E-09) with the maximum adsorption capacity of 330 mg/g. A thermodynamics analysis shows that the adsorption was endothermic, random and spontaneous. The magnetic-PEI-cellulose is able to be regenerated and reused for 4 times with RB5 percentage removal above 70%. In conclusion, magnetic-PEI-cellulose was successfully demonstrated and can be used as a new promising adsorbent for the removal of dye from textile wastewater.